Eight‐Year Retention Rate of First‐Line Tumor Necrosis Factor Inhibitors in Spondyloarthritis: A Multicenter Retrospective Analysis. Issue 6 (June 2017) - Favalli, Ennio Giulio; Selmi, Carlo; Becciolini, Andrea; Biggioggero, Martina; Ariani, Alarico; Santilli, Daniele; Fusaro, Enrico; Parisi, Simone; Massarotti, Marco; Marchesoni, Antonio; Meroni, Pier Luigi
Abstract : Objective: To evaluate the 8‐year survival of the first tumor necrosis factor inhibitor (TNFi) in patients with axial spondyloarthritis (SpA) or psoriatic arthritis (PsA), identify the predictive factors for withdrawal, and compare the discontinuation rates for infliximab, etanercept, and adalimumab. Methods: We evaluated PsA and axial SpA patients treated with a first‐line TNFi between 2005 and 2015 at 4 Italian tertiary centers. Eight‐year drug survival was calculated by the Kaplan‐Meier method, and risk for discontinuation among treatment groups compared by stratified log‐rank test. Univariate and multivariate Cox proportional hazard models were developed to examine predictors of withdrawal. Results: Of 614 patients (316 axial with SpA, 298 with PsA), 203 received adalimumab, 131 etanercept, and 280 infliximab, with similar frequencies in axial SpA and PsA subgroups. The cumulative 8‐year retention rate in the whole population was 55.1% (57.2% and 51.9% for axial SpA and PsA, respectively; P  = not significant). No significant differences were observed in drug persistence among individual TNFi in either group. Male sex (hazard ratio [HR] 0.595 [95% confidence interval (95% CI) 0.405–0.875]; P  = 0.008) and concomitant methotrexate use (HR 0.648 [95% CI 0.426–0.985]; P  = 0.042) were associated with a lower risk of withdrawal in PsA. High baseline Bath Ankylosing Spondylitis Disease Activity Index (HR 0.9842 [95% CI 0.9708–0.9980]; P  = 0.028) was associated with a lower risk of withdrawal in axial SpA. No difference was found in the comparative analysis of reasons for discontinuation between PsA and axial SpA. Conclusion: We reported that the real‐life 8‐year retention rate of the first TNFi in axial SpA and PsA is greater than 50%, with no significant differences between axial SpA and PsA, irrespective of the individual TNFi.